Student Management in Elementary School - Marbun, Rifka Angelina Wati; Ariyanti, Maezora Putri; Andriyanto, Nazwa Ayumi; Linawati; Pertiwi, Santhi (Jurnal Inovasi Pendidikan MH Thamrin, 2025)
Education is an important aspect that requires good management so that educational goals are achieved. In an effort to shape the character of students, the role of parents is very important, but it needs to be supported by formal education at school. Student management is an important part of school management to create an orderly, regular, and comfortable learning process. To achieve the goals of school education, student management includes four activities: new student admissions, learning progress activities, guidance and discipline coaching, and observation. Student management generally functions as a place for students to develop as much as possible in terms of social, individuality, aspirations, needs, and other potentials. This study aims to describe the influence of student management on student learning outcomes. By using the literature review method and reviewing six Sinta-accredited articles in the last five years, it was found that student management has a significant effect on student learning achievement. The role of effective student management includes patient management from registration, during the learning process, to graduation—which makes the teaching and learning process more focused so that it produces high-achieving students. However, the success of this management is also influenced by parental involvement; without their support, the achievement of learning goals cannot be fully realized.